2010
DOI: 10.1002/lary.21183
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid storm in a patient with fulminant hepatic failure

Abstract: This manuscript describes a 28-year-old patient with a history of Graves' disease who was transferred to Tulane University Hospital with fulminant hepatic failure. He reported associated nausea, vomiting, anorexia, as well as jaundice and abdominal discomfort for a period of 3 weeks prior to his admission. His thyroid function tests on admission were TSH, 0.013 μU/mL; T3, 94.9 μU/mL; T4, 9.37 μU/mL; Free T4, >6 μU/mL. His liver function tests were characteristic of hepatic failure. The patient underwent an eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Although there are multiple case reports of cholestasis and severe liver dysfunction presenting in patients with hyperthyroidism, these are mainly adult patients, many of whom have associated comorbid conditions 33–35,46–49 . Additional causes for the liver dysfunction in these patients may include concomitant autoimmune liver disease, drug‐induced dysfunction from antithyroid medication, and/or sepsis 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Although there are multiple case reports of cholestasis and severe liver dysfunction presenting in patients with hyperthyroidism, these are mainly adult patients, many of whom have associated comorbid conditions 33–35,46–49 . Additional causes for the liver dysfunction in these patients may include concomitant autoimmune liver disease, drug‐induced dysfunction from antithyroid medication, and/or sepsis 49 .…”
Section: Discussionmentioning
confidence: 99%
“…There were eight previous reports of Graves' disease complicated with liver failure, and the chief complaints in those cases were caused by Graves' disease. Therefore, this is a rare case in that the liver dysfunction and jaundice primarily appeared before the complication of thyroid storm (Table 2) [5][6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 96%
“…The scientific literature describes some cases of severe cholestasis linked with hyperthyroidism [5][6][7][8][9][10][11]. These cases are often complicated with CHF.…”
Section: Discussionmentioning
confidence: 99%
“…Although PTU is considered first-line treatment for thyroid storm, a known side-effect of this medication is ALF via a proposed hypersensitivity reaction. It has been suggested that PTU is the second most common drug following acetaminophen to cause ALF requiring liver transplantation [ 12 ]. Moreover, methimazole has been rarely associated with hepatotoxicity two to twelve weeks after the onset of therapy.…”
Section: Discussionmentioning
confidence: 99%